EMPOWERMENT OF VOCATIONAL SECONDARY SCHOOL THROUGH STRATEGIC MANAGEMENT : Study about public vocational secondary school exertion to prepare graduates which in accordance with job market needs in Banda Aceh Nanggroe Aceh Darussalam - Murniati, AR (2005)
Focus of this problem is: How the empowerment of Vocational Secondary School (SMK) through strategic management in preparing graduates which in agree with job market need? The object of this research is to find out SMK management profile, strategic management formulation, and strategic management implementation in SMK empowerment. This research used qualitative approach with case study, research subject is: all situation, condition, and SMK environment, headmaster, internal school members, and Vocational Secondary School stakeholders. The theoretical ground in analyzing this research finding is strategic management. This theory based on assumption that strategic management has strong basis in empowering all human resources, so, stakeholders can actively participate to cooperate, to give affirmation to all organization personnel in order to do the task in accord with each task performance demand. This research findings show: First, the three SMK profiles have basic standard as vocational school organization, the three SMK can implement their main task in accordance with basic standard which has been enacted in accordance with vocational school performance, it can be seen from organization structure ordering, curriculum and program, and also the existed resources usage, whether it is human resources or its facility. From the three SMK, SMK Negeri 3 has organization structure that is more detail and more optimal program if it is compared with SMK Negeri 1 and 2. Second, the three SMK initiate the formulation of strategic management by enacting vision, mission, object, goal, so, it facilitates them in directing the achievement of vocational school organization object. Strategy in enacting all sorts of policy is taken through deliberation, but in a particular matters the policy is taken by school head. Third, strategic management implementation which is conducted by SMK is by empowering all internal and external school members proportionally. In terms of strategic management implementation, SMK Negeri 3 more optimizing school personnel roles in implementing their programs. While SMK Negeri 1 and 2 still needs to optimize stakeholders roles actively in order to facilitate them in implementing enacted programs in the efforts to answer job market demand. The findings above describe that strategic management that is applied by Vocational Secondary School in Banda Aceh can empower personnel and internal and external environment. Therefore, this research offers SMK conceptual model of strategic management exertion, by recommending: (1) The needs of empowerment internal schools members through detail and proportional work mechanism in optimizing SMK programs; (2) The needs of headmaster in creating active participation of internal and external school members through effective control mechanism, (3) Conducting socialization of strategic management basic concept in internal and external school environment, in order school goal and customer need is fulfilled simultaneously; (4) The needs of SMK program and curriculum development that can answer job market needs.